Epistemologi ‘Ulum al-Qur'an - Fitriono, Eko Nani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article addresses the issue of the epistemological dynamics and methods in the development of Qur'anic interpretation from the era of Prophet Muhammad to the modern era. The study aims to analyze the transformation of interpretive methods, the validity of traditional and modern epistemologies, and their integration with contemporary scientific philosophy. The research employs a qualitative-descriptive approach with historical, epistemological, and contextual analysis. The findings reveal that interpretive methods have evolved from literal, tradition-based approaches (bi al-ma'tsur) to the use of hermeneutics, scientific philosophy, and contextual approaches to address the challenges of modernity. In the Nusantara context, local interpretations such as the works of Abdurrauf Singkel and Quraish Shihab demonstrate the relevance of Qur'anic interpretation in responding to socio-cultural issues. The study concludes by emphasizing the need for integrating traditional epistemology with modern approaches to produce holistic and contextually relevant interpretations while adhering to the authority of divine revelation.